Promising alternative wild phytofoods to mitigate the environmental aridity and food insecurity in Balochistan Province, NW Pakistan: A cross - cultural approach - Kousar, Shazia; Khan, Nazar; Abbas, Zaheer; Harun, Nidaa; Ishaq, Kamran; Khan, Tahir; Hashem, Abeer; Dolores Avila-Quezada, Graciela; Fathi Abd_Allah, Elsayed (Ethnobotany Research and Applications, 2025)
Background: The current paper elaborates the wild edible plants (WFPs) diversity, associated folk knowledge and cross-cultural comparison of three ethnic groups of the Balochistan Province, Pakistan. Methods: The field trips were carried out in spring 2018 to winter 2020 employing purposive sampling techniques for respondents. We used semi-structured interviews with open ended questions. A total of 195 interviews yielded 140 plant species in 44 families and 105 genera. Results: Family Brassicaceae (10.17%) showed maximum representation with Asteraceae (10%), and Apiaceae (6.42%). Eight used categories i.e. eaten fresh (47 spp. 33.57%), as cooked vegetable (46 spp., 32.85%), vegetable and salad (15 spp, 10.71%), salad (14 spp, 10%), beverages only (8 spp, 5.71%), and flavor (7 spp, 5%) were found based on consumption. Among used parts, leaves (54 spp., 38.57%) were the most used part followed by fruits (44 spp, 31.42%), tubers (13, 9.28%), bulb (11, 7.8% species), whole plant (8, 5.7%), flowers (4, 2.8%), seeds (4, 2.8), shoots (3, 2.14) young stem (2, 1.42). Seventy-five (75) species (53.57%) were cited for commonly by all tribes while the rest 65 (46.42%) differently. Pashtuns hold comparatively significant traditional knowledge and exclusively utilized 44 (31.42%) plant species. Similarly, the Pushtoons and Balochis were sharing 13 (9.28%) plant species. Jaccard index (JI) discovered that 92 plant species have never been reported from the province before for example Ferula costata, F. oopoda, Ferula assa-foetida, Allium zhobicum, Asphodelus tenuifolius, and Menoicus linifolius etc. Conclusion: Effect of age, gender and different inter-cultural folk heterogeneity observed profound impact on overall knowledge volume. Several geo-climatic changes and anthropo-zoogenic factors are causing the fragmentation of existing knowledge. The promotion of these wild edible plants (WFPs) as crops would underpin the food sustainability and socioeconomic development in the current scenario of food insecurity. Key words: food ethnobotany; cross-cultural heritage; arid land; food security; wild edibles